Nitrous oxide for the treatment of psychiatric disorders: A systematic review of the clinical trial landscape. (11th April 2022) - Liu, Helen; Kerzner, Jaimie; Demchenko, Ilya; Wijeysundera, Duminda N.; Kennedy, Sidney H.; Ladha, Karim S.; Bhat, Venkat
Abstract: Objective: To systematically review published research studies and ongoing clinical trials investigating nitrous oxide (N2 O) in psychiatric disorders, providing an up‐to‐date snapshot of the clinical research landscape. Methods: A comprehensive literature search was conducted for studies published until June 2021 using the OVID databases (MEDLINE, Embase, APA PsycInfo) and the clinical trial registries (ClinicalTrials.gov, ICTRP). Results: In total, five relevant published articles were identified, among which four investigated N2 O for depression. One single‐dose randomized controlled trial (RCT) for treatment‐resistant depression (TRD), one triple crossover RCT comparing 50% vs. 25% N2 O for TRD, and one repeated‐dose RCT for major depressive disorder (MDD) suggest that N2 O has preliminary feasibility with rapid‐acting effects on symptoms of depression. From the public registries, 10 relevant ongoing clinical trials were identified. They aim to explore the use of N2 O for MDD, post‐traumatic stress disorder, bipolar disorder, obsessive‐compulsive disorder, and suicidal ideation. To date, the typical treatment protocol parameters were a single session of 50% N2 O delivered for 60 min, although the concentration of 25% is also being explored. Projected enrolment numbers for ongoing trials ( M = 55.0) were much higher than sample sizes for published studies ( M = 13.0), suggesting that there potentially will be more large‐scale RCTs published in the next few years. Conclusion: Preliminary studies support the feasibility of administering N2 O for depression; however, appropriate blinding is a critical challenge. Larger‐scale RCTs with repeated doses of N2 O and follow‐up times beyond 1 month are needed to confirm the feasibility, therapeutic efficacy, and sustainability of response.